Health warning labels on heated tobacco products and their impact on use intentions and risk perceptions: a cross-sectional study of adult tobacco users in the US and Israel - Zongshuan Duan; Hagai Levine; Yael Bar-Zeev; Yuxian Cui; Cassidy R. LoParco; Yan Wang; Lorien C. Abroms; Amal Khayat; Carla J. Berg (BMC, 2023)
Abstract Background Health warning labels (HWLs) represent an evidence-based tobacco control strategy; however, their application to heated tobacco products (HTPs) and related impacts are understudied. This study examined the impact of HTP HWLs on HTP use intentions and risk perceptions among current tobacco users. Methods We analyzed cross-sectional survey data from adults in the US and Israel reporting past-month tobacco use and awareness of HTPs (N = 424). Multivariate analyses examined: (1) sociodemographics in relation to self-reported impact of HTP HWLs (i.e., more concerned about HTP use, reassured, no effect [referent]) among those who noticed HTP HWLs (multinomial regressions); and (2) HWL impacts in relation to HTP use intentions and perceived addictiveness and harm (linear regressions). Results Among participants who noticed HTP HWLs (n = 372, 87.7%), 27.7% reported HWLs increased their concerns about HTP use, 22.6% were reassured about use, and 49.7% reported no effect. Factors associated with increased concern (vs. no effect) included other tobacco product use (aOR = 2.10, 95% CI 1.21-3.64) and being female (aOR = 1.77, 95% CI 1.03-3.05). Factors associated with being reassured about HTPs use (vs. no effect) included current HTP use (aOR = 2.11, 95% CI 1.11-4.00) and being from Israel (vs. US: aOR = 3.85, 95% CI 1.85-7.69), female (aOR = 1.91, 95% CI 1.07-3.42), and less educated (< college education: aOR = 2.57, 95% CI 1.42-4.63). Reporting that HWLs on HTPs increased concern (β = 0.46, 95% CI 0.03-0.89) and reassured of use (β = 0.94, 95% CI 0.47-1.41) were positively associated with HTP use intentions; no associations with risk perceptions were found. Conclusions Findings indicate that most tobacco users noticed HWLs on HTPs, but the majority reported no effect or being reassured of using HTPs, effects that were magnified for specific subgroups. Both increased concern and reassurance correlated with greater use intentions. Additional research should evaluate HTP HWL impacts and ensure effectiveness in communicating risks and discouraging use.